Knowledge of Acne among Medical Students: Pretest and Posttest Assessment. (28th January 2014) - Shivaswamy, Kanakapura Nanjundaswamy; Shyamprasad, Arakali Lakshminarayana; Sumathy, Tharayil Kunneth; Ranganathan, Chandrashekaran; Kumar, Shanmugan Praveen
Abstract : Background. Acne vulgaris is a disorder of sebaceous glands mainly affecting the adolescent population. There are some misconceptions about acne not only in the general population but also among the medical students. Methods. Second year medical undergraduate students attending dermatology postings for the first time were included in the study. A questionnaire (in yes or no answer format) with 20 questions on acne, each carrying one mark, was to be answered by the students. The students were categorized into 4 grades based on the marks obtained: Grade I 90% marks and above, Grade II 75%–90%, Grade III 50%–74%, and Grade IV <50% marks obtained. Results. Of the 144 students of the batch, 95 (69.5%) completed both pretest and posttest questionnaires. The average pretest score was 14.1 and that of the posttest was 16.9. The percentage of improvement in mean score from pretest to posttest was 16.5. Fischer's exact test was applied to analyze the improvement in scores between pretest and posttests which is significant atP = 0.015 (P < 0.05 ). In the pairedt -test the improvement in mean scores between pretest and posttest was significant atP < 0.001 .